The influence of work motivation, job satisfaction, and organizational commitment on the organizational citizenship behavior of employees at the department of tourism and culture - Ronal Regen; Desmita Linda; Hermendizal Hermendizal; Juanda Sasmita; Jufriyanto Jufriyanto (Journal of Educational and Learning Studies, 2022)
This study aims to determine the effect of work motivation, job satisfaction, and organizational commitment on the Organizational Citizenship Behavior of the Employees of the Tourism and Culture Office of Kerinci Regency. This study uses a quantitative research type method, where the sampling technique uses a total sampling technique, with a total sample of 31 employees of the Tourism and Culture Office of Kerinci Regency. The analysis technique is multiple regression analysis. The results of this study are either partially or simultaneously, work motivation, job satisfaction, and organizational commitment have a positive and significant impact on the Organizational Citizenship Behavior of the Kerinci Tourism and Culture Office Employees. The magnitude of the effect is 57.6%.